PENGARUH PROMOSI, STORE ATMOSPHERE, DAN KEMUDAHAN PEMBAYARAN TERHADAP IMPULSE BUYING (Studi Kasus Matahari Department Store Java Supermall Semarang) - Gitanjali Bayumurti; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2018)
The business world is increasingly leading to electronic media, causing the use of online stores (onlineshop) as a medium of purchase transactions of goods or services become increasingly increased rapidly. In e-commerce business competition is required to have capabilities and strategies that can capture opportunities and update the market. Strategies that can be done in the form of E-WOM and E-WEB so as to encourage the increase of E-TRUST that will make E-LOYALTY of customers increases. Type of research used is explanatory research. Sampling technique using Purposive Sampling, the sample used in this research is a student of Faculty of Social and Political Sciences Diponegoro University who had been shopping at Tokopedia online site. Respondents in this study amounted to 100 respondents. The data were collected using a questionnaire using a linkert measurement scale. This research uses path analysis technique by improving the software package of SPSS (Statistical Package for Social Science) version 22.0 which used Validity, Reliability, Cross tab, correlation coefficient, simple regression and multiple regression analysis, significance test (t test and F test.. The results showed that all independent variables in this study had a positive and significant influence on the dependent variable, either partially or simultaneously, while the E-TRUST variable acts as a partial intervening / mediation variable indicating there is indirect influence of E-WOM and E-WEB on E-LOYALTY.